Kajian Kegunaan Google Classroom dalam Meningkatkan Kemampuan Berpikir Kritis Peserta Didik - Jeni Danurahman; Dikdik Baehaqi Arif (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2021)
Education is an effort to educate the nation's life and form humans who can compete in the era of the industrial revolution 4.0. The rapid development of information and communication technology has contributed to the education sector. The purpose of this research is to reveal the abilities that must be possessed by the 21st century, namely the ability to think critically and the ability to operate technology. This study uses a descriptive content analysis method with a type of content analysis designed to describe certain information or text content by analyzing various national, international, and other sources of scientific articles related to the use of Google Classroom during the COVID-19 pandemic in improving students' critical thinking skills. With the findings that the use of google classroom can improve students' critical thinking skills.